Analyzing interactions between the GV1 Cell Line, Juvenile Hormone, and Juvenile Hormone Binding Protein - Sng, Xuan En Joel (My University, 2011)
Insect juvenile hormone (JH) and its hemolymph transport protein, juvenile hormone binding protein (JHBP) play key roles in the development of many insects. However, the exact mechanism via which JH and JHBP regulates development remains unclear. This study proposes an examination of the molecular interactions between JH and JHBP in Manduca sexta GV1 cells and attempts to determine the rate at which GV1 cells metabolize JH to juvenile hormone acid and clarify if JHBP prevents the degradation of JH in vitro.
11 p.
Keywords: Entomology; Biology; Biochemistry